Cognitive decision process: The context of auditors' diagnostic reasoning - Abas, Zakaria (Universiti Utara Malaysia, 1999)
Based on a cognitive psychology framework, this article provides an insight into how auditors perform diagnostic reasoning tasks through an analytical review (AR) process. AR refers to the diagnostic process of identifying, investigating, and resolving unexpected fluctuations in account balances and other financial relationships in financial statements. Auditors performing AR typically follow four distinct components of a diagnostic, sequential and interactive (DSI) process, namely: mental representation, hypothesis generation, information search, and hypothesis evaluation. Through the DSI process, auditors are able to recognize and detect errors and irregularities in financial statements for the purpose of presenting a true and fair view of financial reporting, with the intention of communicating quality and rediable economic information of an enterprise to users.